The feasibility of establishing a free clinic for uninsured patients with neurologic disorders. Issue 4 (August 2015) - Taylor, Joseph J.; Larrew, Thomas; Omole, Armina; Roberts, Mallory; Kornegay, Adam; Kornegay, Kelly; Yamada, Lidia; Revuelta, Gonzalo J.; Sohn, Mimi; Hughes, Thomas; Edwards, Jonathan C.
Abstract : Summary: The Dream Center Neurology Clinic (DCNC) is a free specialty clinic associated with the Medical University of South Carolina that provides health care for uninsured patients with neurologic disorders. Routine neurologic care is often neglected by free primary care clinics, leaving indigent and uninsured patients to suffer from treatable neurologic ailments. The DCNC was established by supplementing existing resources from a free primary care facility called the Dream Center. Our strategy of building a high-need specialty service into a preexisting primary care infrastructure may provide a blueprint for neurologists who are eager to address the neurologic needs of the underserved in their local communities. According to local charge estimates, the DCNC has provided roughly $120, 000 worth of outpatient neurologic care over the past year. The clinic runs through the collaborative effort of medical students as well as academic and private health care providers. Donated services such as EEG, diagnostic lab work, botulinum toxin, supplies, and imaging are also critical to clinic operations. In addition to providing the uninsured with services that are normally inaccessible to them, the DCNC provides a unique educational opportunity for medical students, residents, and all volunteers who are eager to help and learn.